Do plasma neprilysin activity and plasma neprilysin concentration predict cardiac events in chronic kidney disease patients?. Issue 1 (9th April 2018) - Emrich, Insa E; Vodovar, Nicolas; Feuer, Linda; Untersteller, Kathrin; Nougue, Helene; Seiler-Mussler, Sarah; Fliser, Danilo; Launay, Jean-Marie; Heine, Gunnar H
ABSTRACT: Background: Since the introduction of sacubitril/valsartan in clinical cardiology, neprilysin has become a major target for heart failure treatment. Plasma neprilysin concentration has been discussed as a novel biomarker that predicts cardiac events. Natriuretic peptides may inhibit plasma neprilysin. As they accumulate in chronic kidney disease (CKD), we hypothesized that high plasma neprilysin loses its predictive role in CKD patients. Methods: We measured plasma levels of neprilysin concentration, neprilysin activity and brain natriuretic peptide (BNP) in 542 CKD G2–G4 patients within the CARE FOR HOMe study. Patients were followed for predefined endpoints of hospitalization for acute decompensated heart failure and incident atherosclerotic cardiovascular events. Results: During 5.1 ± 2.1 years, 63 patients had acute decompensated heart failure and 125 patients had incident atherosclerotic cardiovascular events. In both Kaplan–Meier and multivariate Cox regression analyses, high plasma BNP and low, rather than elevated, neprilysin activity predicted future hospitalization for acute decompensated heart failure; neprilysin concentration was not predictive. Furthermore, only BNP was an independent predictor of incident atherosclerotic cardiovascular events. Conclusions: In line with experimental studies, high natriuretic peptides may inhibit neprilysin activity in CKD. Therefore, high neprilysin activity and concentrations are not predictors of adverse cardiovascular outcome in CKD patients. Thus neprilysin inhibitors should be implemented with caution in patients with advanced CKD.